The impact of polymer selection and dose on the incorporation of ballasting agents onto wastewater aggregates - Murujew, Olga; Geoffroy, Jordan; Fournie, Emeline; Gioacchini, Elisa Socionovo; Wilson, Andrea; Vale, Peter C. J.; Jefferson, Bruce; Pidou, Marc (Elsevier, 2019)
Ballasted flocculation is an efficient high-rate sedimentation process getting more attention as an advanced P removal technology for levels below 0.1 mg/L. The process is well-known yet only very few studies have investigated the interactions, within the matrix of wastewater, of coagulant, polymer and ballast, especially when it comes to polymer doses and types which are, in the industry, rather based on recommendations than scientific evidence. In this work, the impact of anionic and cationic polymers has been investigated on P removal and floc properties. Anionic polymers showed to be superior to cationic ones when it comes to P removal and doses even as low as 0.01 mg/L yield better results than coagulant alone. There appears to be a “best-case” floc size with which very good P removal (>90%) can be achieved and flocs of sufficient strength can be generated.
Keywords: Phosphorus removal; Ballasted flocculation; Magnetite; Polymer